Bird functional diversity decreases with time since disturbance: Does patchy prescribed fire enhance ecosystem function?. Issue 1 (January 2016) - Sitters, Holly; Di Stefano, Julian; Christie, Fiona; Swan, Matthew; York, Alan
Abstract: Animal species diversity is often associated with time since disturbance, but the effects of disturbances such as fire on functional diversity are unknown. Functional diversity measures the range, abundance, and distribution of trait values in a community, and links changes in species composition with the consequences for ecosystem function. Improved understanding of the relationship between time since fire (TSF) and functional diversity is critical given that the frequency of both prescribed fire and wildfire is expected to increase. To address this knowledge gap, we examined responses of avian functional diversity to TSF and two direct measures of environmental heterogeneity, plant diversity, and structural heterogeneity. We surveyed birds across a 70‐year chronosequence spanning four vegetation types in southeast Australia. Six bird functional traits were used to derive four functional diversity indices (richness, evenness, divergence, and dispersion) and the effects of TSF, plant diversity and structural heterogeneity on species richness and the functional diversity indices were examined using mixed models. We used a regression tree method to identify traits associated with species more common in young vegetation. Functional richness and dispersion were negatively associated with TSF in all vegetation types, suggesting that recent prescribed fire generates heterogeneous vegetation and provides greater opportunities for resource partitioning. Species richness was not significantly associated with TSF, and is probably an unreliable surrogate for functional diversity in fire‐prone systems. A positive relationship between functional evenness and structural heterogeneity was common to all vegetation types, suggesting that fine‐scale (tens of meters) structural variation can enhance ecosystem function. Species more common in young vegetation were primarily linked by their specialist diets, indicating that ecosystem services such as seed dispersal and insect control are enhanced in more recently burnt vegetation. We suggest that patchy prescribed fire sustains functional diversity, and that controlled use of patchy fire to break up large expanses of mature vegetation will enhance ecosystem function.